Proinflammatory Cytokines IL-6 and TNF-α Increased Telomerase Activity through NF-κB/STAT1/STAT3 Activation, and Withaferin A Inhibited the Signaling in Colorectal Cancer Cells - Seyung S. Chung; Yong Wu; Quincy Okobi; Debbie Adekoya; Mohammad Atefi; Orette Clarke; Pranabananda Dutta; Jaydutt V. Vadgama (Mediators of Inflammation)
There are increasing evidences of proinflammatory cytokine involvement in cancer development. Here, we found that two cytokines, IL-6 and TNF-α, activated colorectal cancer cells to be more invasive and stem-like. Combined treatment of IL-6 and TNF-α phosphorylated transcription factors STAT3 in a synergistic manner. STAT3, STAT1, and NF-κB physically interacted upon the cytokine stimulation. STAT3 was bound to the promoter region of human telomerase reverse transcriptase (hTERT). IL-6 and TNF-α stimulation further enhanced STAT3 binding affinity. Stem cell marker Oct-4 was upregulated in colorectal cancer cells upon IL-6 and TNF-α stimulation. Withaferin A, an anti-inflammatory steroidal lactone, inhibited the IL-6- and TNF-α-induced cancer cell invasion and decreased colonosphere formation. Notably, withaferin A inhibited STAT3 phosphorylation and abolished the STAT3, STAT1, and NF-κB interactions. Oct-4 expression was also downregulated by withaferin A inhibition. The binding of STAT3 to the hTERT promoter region and telomerase activity showed reduction with withaferin A treatments. Proinflammatory cytokine-induced cancer cell invasiveness is mediated by a STAT3-regulated mechanism in colorectal cancer cells. Our data suggest that withaferin A could be a promising anticancer agent that effectively inhibits the progression of colorectal cancer.